1986
DOI: 10.1002/eji.1830160822
|View full text |Cite
|
Sign up to set email alerts
|

Presence of IgE suppressor factors in human colostrum

Abstract: In spite of intensive investigations, the ability of breast feeding to delay and to attenuate atopic diseases in children remains debatable. This study documents a mechanism whereby breast feeding might interfere with the synthesis of IgE by breast-fed infants. Indeed, we show that colostrum contains IgE-binding factors (IgE-BF) capable of suppressing the in vitro synthesis of human IgE. Colostrum obtained from 15 donors was successively depleted of lipids and casein, filtered through Amicon XM50 membrane (mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Indeed, the latter was shown to be a single copy gene [20], It was next demonstrated that IgE-BFs are generated by the protoeolytic cleavage of sur face FctR 11 and that they do not derive from an intra cellular post-translational cleavage of Fc,R II precursor molecules [12], The results from ongoing studies suggest that the 45-KD molecule is first trans formed into one of 37 KD which is then successively fragmented into 33-and 25-KD molecules. More over, IgE-BFs with a molecular weight of 16 KD have also been documented in human colostrum as well as in the culture supernatant of B and T cell lines [25].…”
Section: Ige-bfs Are Cleavage Products Of Surface Fc R IImentioning
confidence: 99%
“…Indeed, the latter was shown to be a single copy gene [20], It was next demonstrated that IgE-BFs are generated by the protoeolytic cleavage of sur face FctR 11 and that they do not derive from an intra cellular post-translational cleavage of Fc,R II precursor molecules [12], The results from ongoing studies suggest that the 45-KD molecule is first trans formed into one of 37 KD which is then successively fragmented into 33-and 25-KD molecules. More over, IgE-BFs with a molecular weight of 16 KD have also been documented in human colostrum as well as in the culture supernatant of B and T cell lines [25].…”
Section: Ige-bfs Are Cleavage Products Of Surface Fc R IImentioning
confidence: 99%
“…In addition to binding of IgE, CD23 ex erts lectin-like properties [4], IgE-binding factors or solu ble CD23 are known to be present within several biolog ical fluids. They have been detected within supernatants of B and T cell lines, peripheral blood lymphocytes as well as monocyte-like cell lines (U937) [4], In addition, human sera and colostrum were shown to contain IgE-BF [27]; quite recently it has been reported that epidermal Langer hans cells release sCD23 after stimulation with IFN-y [28].…”
Section: Discussionmentioning
confidence: 99%
“…This protracted period of increased membrane permeability may contribute to the higher incidence of infections (Fergusson et al, 1981;Forman et al, 1984;Goldblum et al, 1996;Myers et al, 1984) and atopic disease (Fallstrom et al, 1984;Lemmert et al, 2006) observed in non-breast-fed infants. A factor in colostrum that suppresses IgE synthesis may also contribute to the lower risk of atopy in breast-fed neonates (Sarfati et al, 1986).…”
Section: Feeding Practices Early In Lifementioning
confidence: 99%